Visualization of core/shell PHBV granules of wild type Comamonas sp. EB 172 in vivo under transmission electron microscope - Mumtaz, Tabassum; Abd. Aziz, Suraini; Abdul Rahman, Nor'aini; Phang, Lai Yee; Wasoh @ Mohamad Isa, Helmi; Shirai, Yoshihito; Hassan, Mohd Ali (Taylor & Francis, 2011)
Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) granule formation in vivo in wild type Comamonas sp. EB172 grown in mixed organic acids under nitrogen limitation were visualized under transmission electron microscope (TEM). The early stages of PHBV production revealed dark-stained mediation elements near the center of the cell supporting the third model of granule formation. The native granules revealed characteristic core-shell structure in which white PHB cores were surrounded by darker PHBV shells. In vitro, the copolymer showed bimodal molecular weight distribution and exhibited two melting peaks in the differential scanning calorimeter (DSC) thermogram, supporting the formation of block copolymer.